Spatial-temporal patterns of flowering asynchrony and pollinator fidelity in hybridizing species of Narcissus - Marquéz, I. (2017)
Speciation requires the evolution of reproductive barriers to achieve isolation between species. In this paper, we examine the role of two major pre-zygotic barriers in reducing the chance of F 1 hybrid formation between two pairs of Narcissus species. Field experiments were performed over 5 years in eight natural populations to determine whether flowering phenology and pollinator fidelity could act as reproductive isolation barriers in Narcissus. Our results show that reproductive isolation due to flowering phenology is highly variable and asymmetric. In some populations, pollinator fidelity was so strong that the quantification of reproductive isolation was complete and a strong negative correlation was found between the strength of this barrier and the abundance of hybrids. Nevertheless, the degree of pollinator fidelity was quite variable among populations indicating that reproductive isolation varies geographically but very consistent across years indicating that plant-pollinator interactions are well established. In fact, the finding that hybrid formation between these species occurs only in sites where pollinator fidelity is incomplete suggests that hybrid formation also varies geographically and that divergent evolutionary outcomes may occur in different sympatric populations of Narcissus. © 2012 Springer Science+Business Media B.V.